Variaciones del tiempo en la escritura de El rastro de Margo Glantz (2020)
In Time and Narration I Paul Ricoeur writes the following: Veo en las tramas que inventamos el medio privilegiado por el que re-configuramos nuestra experiencia temporal confusa, informe y, en el límite, muda (Ricoeur 34). The author rightly indicates the strangeness of the common: an experience of time that can rarely be formulated, it's happening is usually forgotten and, although the effects of its passing leave manifest signs of deterioration (a wrinkled face, for example), such evidence does not make the phenomenon more understandable, instead, it makes it rarer and more disturbing. That is why the words of Saint Augustine in his Confessions are so transparent: Pues, ¿qué cosa es tiempo? Si nadie me lo pregunta, yo lo sé para entenderlo; pero si quiero explicarlo a quien me lo pregunta, confieso que no puedo (324). Thanks to the reflective character of the literary language which creates its own reality...